A practical guide to choral conducting - Rosenbaum, Harold (Routledge, 2018)
Rooted in the experience of a professional choral conductor, this book provides a guide to practical issues facing conductors of choral ensembles at all levels, from youth choruses to university ensembles, church and community choirs, and professional vocal groups. Paired with the discussion of practical challenges is a discussion of over fifty key works from the choral literature, with performance suggestions to aid the choral conductor in directing each piece. Dealing with often-overlooked yet vital considerations such as how to work with composers, recording, concert halls, and choral tours, A Practical Guide to Choral Conducting offers a valuable resource for both emerging choral conductors and students of choral conducting at the undergraduate and graduate levels.
Keywords: Choral conducting; kuorolaulu; johtaminen; kuorot